Analysis Of The Influence Of Work Motivation, Work Environment And Job Stress On Employee Performance Of National Food Retail Companies - Eva Yuniarti Utami; Heri Susanto; Sunarto; Besse Faradiba; Loso Judijanto (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2024)
The purpose of this study is to examine the potential effects of work environment, motivation, and stress on employee performance. All of the participants in this study are employees. The saturation sampling strategy is employed in this study. The study's sample comprised one hundred participants. In this study, the methods of gathering data were observation and questionnaires. To make inferences about the issue being researched, the data gathered from the completed questionnaire is subsequently processed and examined with the aid of data processing techniques. Multiple regression analysis, descriptive testing, classical assumption testing, and data quality testing are all used in this study's data analysis methodology. The following findings are derived from the data that was gathered and examined using a multiple linear regression model: Employee performance is influenced by the workplace. Employee performance is influenced by work motivation. The impact of job stress on employee performance is zero. Workplace motivation, work atmosphere, and job stress all affect how well employees perform.